A qualitative investigation of perceived impacts of virtuality on effectiveness of hybrid construction project teams. Issue 1 (2nd January 2018) - Hosseini, M. Reza; Bosch-Sijtsema, Petra; Arashpour, Mehrdad; Chileshe, Nicholas; Merschbrock, Christoph
Abstract : Purpose: The "virtuality" of a team collaborative interaction is the extent to which it is accomplished in the same place, in fully distributed virtual teams, or in a hybrid combination of the two. However, existence, strength and process of potential association between virtuality and effectiveness in construction project teams have remained elusive. This paper aims to address this gap in the literature. Design/methodology/approach: In this study, a conceptual model demonstrating the association between virtuality and effectiveness of teams was developed through integrating the input-process-output (IPO) model and the "Big Five" theory. This conceptual model was contextualised for the construction industry drawing upon conducting 17 semi-structured interviews with hybrid team experts. Findings: The findings provide the first model mapping the associations between virtuality and dimensions of team effectiveness for the construction context. Practical implications: The discovered patterns of associations between virtuality and dimensions of effectiveness for hybrid construction project teams (HCPTs) will assist managers in designing and running more effective teams. In addition, the findings help construction practitioners better understand how virtuality influence the performance and satisfaction of team members in HCPTs. The present study concludes with outlining a set of recommendations based on the findings of the study. Originality/value: As the first study in its kind, the present study offers a new insight into the concept and impacts of virtuality for construction teams and provides instructions and guidelines for designing and maintaining the effectiveness of such teams on construction projects.